FORMATION OF A HEALTHY LIFESTYLE IS THE KEY TO HEALTH - Sokhiba Israilova Buribaevna (Web of Journals Publishing, 2024)
Forming and maintaining a healthy lifestyle is the main guarantee of general health and well-being. A healthy lifestyle includes a set of habits and practices that promote physical, mental, and emotional well-being. By making healthy lifestyle choices, people can increase their quality of life, reduce their risk of chronic disease, and improve overall health outcomes. This article provides information about the health guarantee of a healthy lifestyle.
Keywords: healthy lifestyle, food, physical education, healthy eating, movement.